Elucidation of the Binding Regions of PAI-1 Neutralizing Antibodies Using Chimeric Variants of Human and Rat PAI-1 - Bijnens, A. P.; Ngo, T. H.; Gils, A.; Dewaele, J.; Knockaert, I.; Stassen, J. M.; Declerck, P. J. (Thrombosis and Haemostasis, 2001)
Increased levels of plasminogen activator inhibitor-1 (PAI-1), the main physiological inhibitor of tissue-type plasminogen activator (t-PA) in plasma, are a known risk factor for thromboembolic and cardiovascular diseases. The elucidation of the binding site of inhibitory monoclonal antibodies may contribute to the rational design of PAI-1 modulating therapeutics. In this study, homolog-scanning mutagenesis was used to identify the binding region of a variety of human PAI-1 inhibitory antibodies, lacking cross-reactivity with rat PAI-1. Therefore, eight chimeric human/rat PAI-1 variants, containing rat PAI-1 substitutions at the N-terminal or C-terminal end with splicing sites at positions 26, 81, 187, 277 or 327, were generated and purified. Biochemical characterization revealed that all chimeras were folded properly. Subsequently, surface plasmon resonance was used to determine the affinity of various monoclonal antibodies for these chimera. Comparative analysis of the affinity and ELISA data allowed the identification of the major binding region of the inhibitory antibodies MA-8H9D4, MA-33B8F7, MA-44E4, MA-42A2F6 and MA-56A7C10. Thus, three segments in human PAI-1 containing each at least one site involved in the neutralization of PAI-1 activity could be identified, i.e. (1) the segment from residue 81 to residue 187 (comprising -helices hD, hE and hF, -strands s4C, s3A, s2A and s1A and the loops connecting these elements), (2) the segment between residues 277 and 327 (hI, thIs5A, s5A and s6A) and (3) the region C-terminal from amino acid 327, including the reactive site loop. The current data, together with previous data, indicate that PAI-1 contains at least four different regions that could be considered as putative targets to modulate its activity.
Keywords: PAI-1; epitope; chimera; antibody; serpin